PENYULUHAN DAN PEMBAGIAN BROSUR KOSMETIK AMAN KEPADA MASYARAKAT DI GOR AGUS SALIM PADANG - Ferilda, Siska; Fendri, Sandra Tri Juli; Fitriasti, Betty (Jurnal Abdimas Saintika, 2024)
This community service was carried out to increase public knowledge regarding the use of safe cosmetics, carried out by providing counseling and brochures regarding safe cosmetics to 43 people at GOR Agus Salim Padang on May 12 2024. After carrying out this activity, it was seen that there was an increase in the knowledge of the community who received counseling and This brochure can be seen by asking about the level of knowledge regarding safe cosmetics before and after the educationKeywords:  Safe Cosmetic, Cuonseling, Brochures